A Cohort Study on the Correlation Between Serum Uric Acid Trajectory and New-Onset Hypertension Based on Longitudinal Health Examination Data in Henan Area - Sheng S; Chen J; Zhang Y; Li W; Li F; Gou R; Tang L; Ding S (Journal of Inflammation Research, 2024)
Shifeng Sheng,1 Jingfeng Chen,1 Yuheng Zhang,1 Weikang Li,1 Feifei Li,1 Rong Gou,2 Lin Tang,2 Suying Ding1 1Health Management Center, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 2Department of Nephropathy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of ChinaCorrespondence: Lin Tang, Department of Nephropathy, The First Affiliated Hospital of Zhengzhou University, No. 1 Longhu Middle Ring Road, Jinshui District, Zhengzhou, 450052, People’s Republic of China, Tel +86 13783623040, Email tanglin@zzu.edu.cn Suying Ding, Health Management Center, The First Affiliated Hospital of Zhengzhou University, No. 1 Longhu Middle Ring Road, Jinshui District, Zhengzhou, 450052, People’s Republic of China, Tel +86 15838023097, Email fccdingsy@zzu.edu.cnObjective: To explore the correlation between serum uric acid (SUA) trajectories and new-onset hypertension, to provide scientific basis for the prevention and treatment of hypertension.Methods: The study cohort was composed of 4372 subjects who met the inclusion criteria in the cohort study of Henan physical examination population. According to the SUA values of the subjects’ physical examination from 2017 to 2019, three different SUA trajectory groups were determined by R LCTM tools, namely low stability group, medium stability group and high stability group. The incidence of hypertension during physical examination in 2020 was followed up, the cumulative incidence rate in each group was calculated by product limit method, and the correlation between different SUA trajectories and new-onset hypertension was analyzed by Cox proportional hazards regression model.Results: The incidence rate of hypertension increased with the increase of SUA locus, which was 4.65%, 9.18% and 12.43% respectively, and the difference was statistically significant (P< 0.001). After adjusting multiple confounding factors, such as gender, waist circumference (WC), blood pressure, body mass index (BMI), fasting plasma glucose (FPG) and blood lipid by Cox proportional hazards regression model, the risk of hypertension in SUA medium stability and high stability group was still 1.476 times ( 95% CI: 1.089~2.000) and 1.692 times ( 95% CI: 1.152~2.484) of low-stable SUA group (P< 0.05).Conclusion: The risk of hypertension increases with the increase of SUA level in the long-term normal range. It is necessary to carry out the intervention for hypertension with long-term normal high value to avoid the progress of hypertension disease, to achieve the purpose of early prevention of hypertension.Keywords: uric acid, hypertension, trajectories, correlation, health physical examination